Optimisation of solar panel efficiency for Solar powered vehicle (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The aim of the project is to increase the efficiency of the solar panel. Solar technology offers great potential in terms of supplying the world’s energy needs. The effective way of utilizing sunlight with solar energy concentration technology and recent developments of its applications using Fresnel lens and water cooling method is reviewed in this project .The increased efficiency saves the number of solar panels used and also its cost efficient. This increased efficient solar panel can be used for several purposes either domestic applications and also industrial applications. In our project we are going to optimize the efficiency of the solar panel using the water cooling method and Fresnel lens and implement them in the solar power vehicle for more power output with less power input.